The complete mitochondrial genome of Shizothorax grahami (Cypriniformes: Cyprinidae) - Zheng, Zonglin (Mitochondrial DNA B Resour, 2016)
Shizothorax grahami (S. grahami) is an underlying economic cold-freshwater fish in southwest China. In this study, the complete mitochondrial genome of S. grahami was determined (GenBank accession number is NC_029708). The mitochondrial genome sequence of S. grahami was a circular molecule with 16,584 bp in length, and contained 37 typical animal mitochondrial genes including 2 ribosomal RNA genes, 13 protein-coding genes, 22 transfer RNA genes and a control region (D-loop). Four nucleotide compositions and their relative proportions of the entire mitogenome was 27.14% C, 19.93% G, 29.58% A and 25.34% T. Among most species of genus Shizothorax, Schizothorax davidi had the closest relationship with S. grahami, and then Schizothorax prenanti.